SWOT Analysis for Business Strategy Development : Analisis SWOT untuk pengembangan Strategi Bisnis - M Yasfin Aqil; Pinky Nadya Maharani; Agung Wibowo; Via Rifqi Andini; Intisar Salwa Khalidah (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) faced by PT Karya Tantri Abadi, a microfinance company that focuses on the economic empowerment of small communities. The research method uses a qualitative approach with interviews and surveys to explore information from employees and customers. The results of the analysis show that the company's strength lies in its fast service without guarantees and good reputation among customers, while the main weakness is the lack of digitalization and financial literacy of the community. Opportunities include entrepreneurial trends and government support, while threats come from competition with formal financial institutions. The proposed strategies include operational digitalization, product diversification, and increasing people's financial literacy. This research makes a significant contribution in formulating sustainable and inclusive business strategies.